Methodological principles of construction of the automated system of technological preparation of manufacture - Бабак, В.П.; Павленко, П.М. (Proceedings of National Aviation University (archive), 2005)
The analysis of major factors is submitted which need to be taken into account at construction of the automated systems. The base principles of construction of the automated systems of technological preparation of manufacture are formulated.